"OUT OF PLACE" IN THE CITY: DEVELOPMENT OF SOCIOSPATIAL DISORDER SENSITIVITY SCALE IN URBAN SETTINGS. Issue 2 (March 2017) - Jaśkiewicz, Michał; Besta, Tomasz
Abstract : The construction and validation of an original scale was pursued to measure individual differences within perception of order violation in the city. It was assumed that socio‐spatial order may beviolated by two categories of situations: (a) when in a given place there is a person who is not an expected and desired user of the space or/and (b) when the place is utilized in a manner different than expected. In two studies ( N = 696 and N = 74) reliability and construct validity of the scale was assessed. In study 1, principal component analysis as well as confirmatory factor analysis confirmed factorial structure in line with our presumptions. Additionally, sociospatial disorder sensitivity was predicted by bonding social capital (inversely), quality of neigbourhood ties (inversely) and level of city identification. In study 2, Space Intrusion subscale was a predictor of the negative feeling toward the target person behaving according to the definition of SI (unwelcome presence of certain category of people e.g., beggars, homeless), whereas Place Transgression scale was a predictor of the negative emotions toward the person violating norms of behaviors and meanings assigned to a place.